2018
DOI: 10.1128/aac.00727-18
|View full text |Cite
|
Sign up to set email alerts
|

Spread of bla CTX-M-15 -Producing Enterobacteriaceae and OXA-23-Producing Acinetobacter baumannii Sequence Type 2 in Tunisian Seafood

Abstract: Bivalves are filter-feeding animals and markers of bacterial pollution. We report a massive spread of through dominant and lineages and/or plasmid subtypes (F31:A4:B1) as well as the presence of OXA-23-producing sequence type 2 (ST2) in seafood, highlighting a direct risk for the consumer. These findings should urge authorities to consider hospital effluents, and also farm and urban effluents, as important sources of extended-spectrum-beta-lactamase (ESBL)/carbapenemase producers that filter-feeding animals ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Our study revealed that 1.4% of fish and 1.6% of clams bought from retail markets in Tunisia were contaminated with ESBL-producing Enterobacterales. Two previous Tunisian studies reported much higher proportions of ESBL-producing Enterobacterales in seafood: the first study identified ESBL-producing bacteria in 65% (52/80) of the tested pools of mussels, 8.3% (3/36) of oysters, and 14.4% (26/181) of clams [ 8 ], while the second one reported 46.8% of ESBL-producing Enterobacterales in fish from the Bizerte lagoon [ 19 ]. The proportions found in this study were lower than what was reported from fish in India (70% of E. coli and 25% of K. pneumoniae ) [ 20 ] and from imported fish in Saudi Arabia (27.2%, 110/405) [ 21 ], similar to what was observed from farmed fish in China (1.5%, 3/218) [ 22 ], and higher than what was reported from seafood in Norway (2/549, 0.4%) [ 6 ] and from Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that 1.4% of fish and 1.6% of clams bought from retail markets in Tunisia were contaminated with ESBL-producing Enterobacterales. Two previous Tunisian studies reported much higher proportions of ESBL-producing Enterobacterales in seafood: the first study identified ESBL-producing bacteria in 65% (52/80) of the tested pools of mussels, 8.3% (3/36) of oysters, and 14.4% (26/181) of clams [ 8 ], while the second one reported 46.8% of ESBL-producing Enterobacterales in fish from the Bizerte lagoon [ 19 ]. The proportions found in this study were lower than what was reported from fish in India (70% of E. coli and 25% of K. pneumoniae ) [ 20 ] and from imported fish in Saudi Arabia (27.2%, 110/405) [ 21 ], similar to what was observed from farmed fish in China (1.5%, 3/218) [ 22 ], and higher than what was reported from seafood in Norway (2/549, 0.4%) [ 6 ] and from Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the poultry sector has been under particular scrutiny due to elevated proportions of ESBL-producing Enterobacterales both in chicken and chicken meat [ 3 , 4 , 5 ]. On the contrary, the presence of MDR Enterobacterales in seafood products has been much less described, although studies in this field show the interest of an increased surveillance [ 2 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 31 Besides, another study reported the emergence of OXA-23 producing Acinetobacter baumannii ST2 in seafood collected from Bizerte lagoon that was contaminated by hospital effluents. 32 This wide spread of OXA-23 producing clone has been recently detected among two fish belonging to the Pagellus acarne species fished in the Mediterranean Sea of Algeria, near Bejaia, which is about 626.3 km away from Bizerte. 33 The emergence and spread of carbapenem-resistant Gram-negative bacteria in the aquatic environment in Tunisia, as well as all over the world, poses an alarming concern.…”
Section: Carbapenemase Producing Gram-negative Bacteria From Other Ormentioning
confidence: 87%
“…Marine bivalves could be potential tools for monitoring of resistant E. coli as well as other Enterobacteriaceae species present in the marine environment at time of sampling (Paper I and II). Several studies have shown the presence of antibiotic resistant E. coli strains obtained from bivalves in other countries, such as Sweden (Bighiu et al, 2019), France , Italy (Vignaroli et al, 2016) and Tunisia (Mani et al, 2018). This suggests that bivalves containing antibiotic resistant E. coli could represent a possible risk of transmission.…”
Section: Marine Bivalves As Tools For the Monitoring Of Antibiotic Resistancementioning
confidence: 99%